A history of the Reformation ; v.2 - Lindsay, Thomas Martin, 1843-1914. (Edinburgh, Scotland : T. and T. Clark, 1908)
Contents : v.2 : The Reformation in Switzerland, France, the Netherlands, Scotland and England; the Anabaptist and Socinian Movements; the Counter-Reformation. Includes bibigraphical references and indexes. Map in back cover.
1956 reprint.
Keywords: Reformation